Feeding Infants Formula With Probiotics or Milk Fat Globule Membrane: A Double-Blind, Randomized Controlled Trial - Li, Xiaonan; Peng, Yongmei; Li, Zailing; Christensen, Britt; Heckmann, Anne B.; Stenlund, Hans; Lönnerdal, Bo; Hernell, Olle (Frontiers in Pediatrics, 2019)
Purpose: To evaluate effects on growth and infection rates of supplementing infant formula with the probiotic Lactobacillus paracasei ssp. paracasei strain F19 (F19) or bovine milk fat globule membrane (MFGM). Methods: In a double-blind, randomized controlled trial, 600 infants were randomized to a formula supplemented with F19 or MFGM, or to standard formula (SF). A breastfed group was recruited as reference (n=200). The intervention lasted from age 21±7 days until 4 months, and infants were followed until age one year. Results: Both experimental formulas were well tolerated and resulted in high compliance. The few reported adverse events were not likely related to formula, with the highest rates in the SF group, significantly higher than for the F19-supplemented infants (p=0.046). Weight or length gain did not differ during or after the intervention among the formula-fed groups, with satisfactory growth. During the intervention, overall, the experimental formula groups did not have more episodes of diarrhea, fever, or days with fever than the breastfed infants. However, compared to the breastfed infants, the SF group had more fever episodes (p=0.021) and days with fever (p=0.036), but not diarrhea. Compared with the breastfed group, the F19 -supplemented infants but not the other two formula groups had more visits/unscheduled hospitalizations (p=0.015) and borderline more episodes of upper respiratory tract infections (p=0.048). Conclusions: Both the MFGM- and F19-supplemented formulas were safe and well tolerated, leading to few adverse effects, similar to the breastfed group and unlike the SF group. During the intervention, the MFGM-supplemented infants did not differ from the breastfed infants in any primary outcome.